Music for film - Fitawater, William; First Light Video Publishing; Australia Film, Television & Radio School; TMW Media Group, Inc. (Venice, CA. : First Light Video Publishing : TMW Media Group, Inc. (distributor), 1990)
Featuring Ron Goodwin's seminar on the procedures and techniques for making motion picture music
Title from title screen
Keywords: Motion picture music; Motion pictures and music